Kearifan Lokal Masyarakat Sub-Sistem Drainase Bringin Dalam Menghadapi Banjir - Waskitaningsih, Novida (Magister Pembangunan Wilayah dan Kota,Undip, 2012)
Community based early warning system is one of the efforts in reducing flood risk by increasing community awareness in managing disasters. The system comprises the reduction of risk level and vulnerability, along with the strengthening of community capacity among others related to local wisdom. Practicing local wisdom in flood management ensures the effectiveness of the early warning system to be implemented. The article identifies the local wisdom found in local communities in seven sub-districts of Semarang City’s Bringin Drainage Sub-system to understand the community’s capacity in developing the flood early warning system. The observation on the methods carried out in flood prediction, information dissemination and emergency evacuation processes showed that the local communities have indeed implemented a conventional early warning system, however the system is not accompanied by clear procedures, rendering current efforts in risk reduction ineffective.